Measuring the accuracy of a point system to diagnose tuberculosis in children with a negative smear or with no smear or culture - Constantino Giovani Braga Cartaxo; Laura C. Rodrigues; Carolina Pinheiro Braga; Ricardo Arraes de Alencar Ximenes (Springer, 2019)
In Brazil, a scoring system was adopted to diagnose tuberculosis in childhood. This study determined the accuracy in diagnosing tuberculosis in children with either a negative smear or with no smear or culture conducted in a reference center in João Pessoa Paraíba - Brazil. It is a phase III validation study, using a cross-section design. The study population consisted of 167 patients attending the outpatient clinics suspected of having tuberculosis. The reference standard for the diagnosis of tuberculosis was a blind and independent review of the medical records, radiology and tuberculin test by two experts. Of the 167 patients, 60 were considered to have tuberculosis (by the reference standard diagnostics). The results for the scoring system with the cut-off of 30 points were: sensitivity 78.57% (95%-CI: 65.56-88.41%), specificity 69.16% (95%-CI: 59.50-77.73%), positive predictive value (PPV): 57.14% (95%-CI: 45.35-68.37%), negative predictive value (NPV): 86.05% (95%-CI: 76.89-92.58%), likelihood ratio (+): 2,55, pre-test probability: 34.36%, and post-test probability (+): 57.14%. This supports the current recommendation for the use of this scoring system in Brazil and similar sites with the cut-off of 30 points. However, as the discriminatory power of the point scoring system may vary across settings, it would be advisable to replicate this phase III study in different settings.